Acid rain and NO2 concentration in Peninsular Malaysia 2020 / Zal Aidi Che Idrus ... [et al.] - Che Idrus, Zal Aidi; Mohd Amin, Muhammad Ameerul Hakim; Shahadan, Muhammad Luthfi; Radzuan, Muhammad I'mran; Mohd Nizam, Muhammad Amirullah; Zulhilm, Nur Aqilah; Efendy, Iman Nuryasmin Iffli; Mohammad Salim, Pauziyah (College of Built Environment, 2023)
Acid rain is an environmental phenomena that can exists due to rapid modernization and increase of development activities without the consideration of environmental aspects.